Concurrency in modula-2 - Sewry, David Andrew (Rhodes University, Faculty of Science, Department of Computer Science, 1985)
A concurrent program is one in which a number of processes are considered to be active simultaneously . It is possib l e to t hink of a process as being a separate sequential program executing independently of other processes, although perhaps communicating with them at desired pOints . The concurrent program, as a whole, can be executed in one of two ways: il ii) in true concurrent manner, wi th each process executing on a dedicated processor in a quasi - concurrent manner, where a processor's processes . time is multiplexed between single the There are two motivations for the study of concurrency in programming languages : i) concurrent programming facilities can be exploited in systems where one has more t han one processor . As technology i mproves, machines having multiple processors will proliferate ii) concurrent p r ogramming facilities may allow programs to be structured as independent , bu t co - operating, processes which can then be implemented on a single processor system . This structure may be more natural to the programmer then the traditional sequential structures. An example is provided by Conway's - 1- Clearly, languages Pascal) problem [Ben82] . by their very nature, traditional sequential- type (Fortran, Basic, Cobol and earlier versions of prove inadequate for the purposes of concurrent programming without considerable extension (which some manufacturers have provided, rendering their compilers non standard-conforming). The general convenience of high level languages provides strong motivation for their development for rea l time programming. Modula - 2 [Wir83] is but one of a number of such r ecently developed languages, designed not only to fulfil a "sequential" role but also to offer facilities for concurrent programming. Developed by Niklaus Wirth in 1979 as a successor to Pascal and Modula, it is intended to serve under the banner of a generalpurpose systems - implementation language. This thesis investigates concurrency i n Modula - 2 and takes the following form: i ) an analYSis of the concurrent facilities offered ii) problems and difficulties associated with these facilities iii) improveme nts and enhancements, including the feasibility of using Modula - 2 to simulate constructs found in other languages, such as the Hoare monitor [Hoa74] and the Ada rendezvous [Uni81]. - 2- Each section concludes with an appraisal of the work conducted in that section . The final section consists of a critical assessment of those Modula - 2 language constructs and facilities provided for the implementation of concurrency and a brief look at concurrency in Modula, Modula-2's predecessor. - Introduction.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Modula-2 (Computer program language); Programming languages (Electronic computers); Computer multitasking